The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/tp.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal error processing in depressive states: a translational examination in humans and rats

Abstract: Depression has been associated with poor performance following errors, but the clinical implications, response to treatment and neurobiological mechanisms of this post-error behavioral adjustment abnormality remain unclear. To fill this gap in knowledge, we tested depressed patients in a partial hospital setting before and after treatment (cognitive behavior therapy combined with medication) using a flanker task. To evaluate the translational relevance of this metric in rodents, we performed a secondary analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Building on these clinical findings, we reported that rats given corticotropin-releasing factor, a peptide that causes myriad signs of stress and depression in humans and laboratory animals, in an attention task showed similar reductions in posterror accuracy. This effect was attenuated by JDTic, a kappa-opioid receptor antagonist with antidepressant-like effects (Beard et al, 2015). These findings indicate that depression-like impairments in cognitive control can be recapitulated in rodents and are sensitive to classes of drugs under investigation for treating depression, opening exciting translational avenues.…”
Section: Funding and Disclosurementioning
confidence: 79%
“…Building on these clinical findings, we reported that rats given corticotropin-releasing factor, a peptide that causes myriad signs of stress and depression in humans and laboratory animals, in an attention task showed similar reductions in posterror accuracy. This effect was attenuated by JDTic, a kappa-opioid receptor antagonist with antidepressant-like effects (Beard et al, 2015). These findings indicate that depression-like impairments in cognitive control can be recapitulated in rodents and are sensitive to classes of drugs under investigation for treating depression, opening exciting translational avenues.…”
Section: Funding and Disclosurementioning
confidence: 79%
“…Specifically, prior research using Eriksen Flanker and Stroop paradigms in acute MDD have shown evidence of poorer post-error adjustments (Beard et al, 2015), abnormal ERN (Chiu and Deldin, 2007) and Pe amplitudes (Schrijvers et al, 2008; Olvet et al, 2010), as well as disrupted frontocingulate activation (Holmes and Pizzagalli, 2008), and neuroimaging studies have consistently observed depression-related deficits in regions of the dlPFC, dmPFC and ACC (Fitzgerald et al, 2008) that may contribute to these impairments. These regions are known to be highly sensitive to stress-related excesses in catecholamine and glucocorticoid levels (Arnsten, 2009), and this may explain the exacerbation of prefrontal dysfunction in stress-sensitive populations, such as those with rMDD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ruminative thinking and poor regulation of sad mood are associated with difficulty disengaging from negative information and modifying behavior accordingly. For example, on tests of performance monitoring that require rapid, accurate responding (e.g., the Eriksen Flanker task), individuals with MDD perform poorly on trials following a commission error (Holmes and Pizzagalli, 2008; Beard et al, 2015), indicating the presence of an oversensitive error-detection system, or a failure to recruit control systems to adaptively respond to errors.…”
Section: Introductionmentioning
confidence: 99%
“…In this latter instance, these manipulations did not affect choice behavior, suggesting that the mechanisms through which increased CRF transmission alters choice latencies may be dissociable from those involved in biasing the direction of choice. Notably central CRF infusions have been reported to increase choice latencies during tests of attention ( Van't Veer et al, 2012;Beard et al, 2015). These findings suggest that the ability of acute stress to induce 'indecisiveness' and increase processing times for action selection is also mediated in part by increased central CRF transmission.…”
Section: Cognitive/motivational Alterations Induced By Increased Crf mentioning
confidence: 94%